Running-specific prostheses permit energy cost similar to nonamputees - Brown, M. B.; Millard-Stafford, M. L.; Allison, A. R. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The purpose of this study was to examine the physiological responses of AMP using a run-specific prosthesis (RP) versus a traditional prosthesis (P) and cross-referenced with nonamputee controls (C) matched by training status, age, gender, and body composition during level treadmill running (TM).